Conducting Polymers as Electrode Coatings for Neuronal Multi-electrode Arrays. Issue 2 (February 2017) - Aqrawe, Zaid; Montgomery, Johanna; Travas-Sejdic, Jadranka; Svirskis, Darren
Abstract : In this new era of bioelectronics, refining transduction pathways between biological systems and electrodes is becoming an increasingly important task. This forum provides insights on how conducting polymer electrode coatings provide more sensitive and compatible systems for recording between the nervous system and electronics.